Numerical analyses in the design of umbrella arch systems - J. Oke (Journal of Rock Mechanics and Geotechnical Engineering, 2014)
Due to advances in numerical modelling, it is possible to capture complex support-ground interaction in two dimensions and three dimensions for mechanical analysis of complex tunnel support systems, although such analysis may still be too complex for routine design calculations. One such system is the forepole element, installed within the umbrella arch temporary support system for tunnels, which warrants such support measures. A review of engineering literature illustrates that a lack of design standards exists regarding the use of forepole elements. Therefore, when designing such support, designers must employ complex numerical models combined with engineering judgement. With reference to past developments by others and new investigations conducted by the authors on the Driskos tunnel in Greece and the Istanbul metro, this paper illustrates how advanced numerical modelling tools can facilitate understanding of the influences of design parameters associated with the use of forepole elements. In addition, this paper highlights the complexity of the ground-support interaction when simulated with two-dimensional (2D) finite element software using a homogenous reinforced region, and three-dimensional (3D) finite difference software using structural elements. This paper further illustrates sequential optimisation of two design parameters (spacing and overlap) using numerical modelling. With regard to capturing system behaviour in the region between forepoles for the purpose of dimensioning spacing, this paper employs three distinctive advanced numerical models: particle codes, continuous finite element models with joint set and Voronoi blocks. Finally, to capture the behaviour/failure ahead of the tunnel face (overlap parameter), 2D axisymmetric models are employed. Finally, conclusions of 2D and 3D numerical assessment on the Driskos tunnel are drawn. The data enriched case study is examined to determine an optimum design, based on the proposed optimisation of design parameters, of forepole elements related to the site-specific considerations.